«
  
»
Como resolver essa equação x elevado ao quadrado - 4x + 3 = 0


RESOLVENDO

X²-4x+3=0
Δ=b²-4ac
Δ=16-12
Δ=4
√Δ=√4
√4=± 2
\( x’= \frac{4+2}{2} = \frac{6}{2} =3 \)
\( x"= \frac{4-2}{2}= \frac{2}{2} =1 \)
S={1,3}

Por Bhaskara
\( x = \frac{-b \pm \sqrt{b^2 -4*a*c}}{2*a} \)
a=1, b=−4, c=3
Δ=b2−4ac
Δ=(−4)2−4*(1)*(3)
Δ=16−12
Δ=4
\( x = \frac{-b \pm \sqrt{\triangle}}{2*a} \\ \\ x = \frac{-(-4) \pm \sqrt{4}}{2*1} \\ \\ x = \frac{4 \pm \sqrt{4}}{2} \\ \\ \\ x’ = \frac{4 + 2}{2} \\ \\ x’ = \frac{6}{2} \\ \\ x’ = 3 \\ \\ \\ x’’ = \frac{4 - 2}{2} \\ \\ x’’ = \frac{2}{2} \\ \\ x’’ = 1 \)
S ={3, 1}



O que achou desse conteúdo? Deixe seu comentário
TAREFAS SIMILARES: